2020
DOI: 10.1177/0963689720945677
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Derived from Human Umbilical Cord Mesenchymal Stromal Cells Protect Cardiac Cells Against Hypoxia/Reoxygenation Injury by Inhibiting Endoplasmic Reticulum Stress via Activation of the PI3K/Akt Pathway

Abstract: Endoplasmic reticulum (ER) stress is implicated in the pathogenesis of many diseases, including myocardial ischemia/reperfusion injury. We hypothesized that human umbilical cord mesenchymal stromal cells derived extracellular vesicles (HuMSC-EVs) could protect cardiac cells against hyperactive ER stress induced by hypoxia/reoxygenation (H/R) injury. The H/R model was generated using the H9c2 cultured cardiac cell line. HuMSC-EVs were extracted using a commercially available exosome isolation reagent. Levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…EVs are involved in intracellular communication, and transfer information via a diverse cargo of cytokines, membrane-trafficking molecules, chemokines, heat shock proteins and even mRNAs and microRNAs, which trigger myriad responses in target (recipient) cells including cardiac cells ( Wu et al, 2020 ). In the setting of cardiac disease, EVs secreted by MSCs from different tissue origins have been demonstrated to mitigate ischemia/reperfusion (I/R) injury in different experimental models of AMI and I/R ( Lai et al, 2010 ; Bian et al, 2014 ; Takov et al, 2020 ; Wu et al, 2020 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…EVs are involved in intracellular communication, and transfer information via a diverse cargo of cytokines, membrane-trafficking molecules, chemokines, heat shock proteins and even mRNAs and microRNAs, which trigger myriad responses in target (recipient) cells including cardiac cells ( Wu et al, 2020 ). In the setting of cardiac disease, EVs secreted by MSCs from different tissue origins have been demonstrated to mitigate ischemia/reperfusion (I/R) injury in different experimental models of AMI and I/R ( Lai et al, 2010 ; Bian et al, 2014 ; Takov et al, 2020 ; Wu et al, 2020 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also explored the use of MSC-derived exosomes as a substitute for MSCs to improve product consistency 63 . Exosomes contain a wide spectrum of biologically active factors, such as cytokines, growth factors, and miRNAs.…”
Section: Possible Causes Of Suboptimal Clinical Trial Results and The Possible Solution To Overcome These Hindrancesmentioning
confidence: 99%
“…AC16 human cardiomyocytes were purchased from the American Type Culture Collection (ATCC, Rockville, MD, USA), cultured in DMEM added 10% FBS, 100 U/mL streptomycin, and 100 U/mL penicillin, and incubated at 37°C in an incubator filled with 5% CO 2 . ExoQuick-TC (System Biosciences, CA, USA) was used for HuMSC-EVs isolated as described previously ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that MSC-derived EVs can mimic the biological characteristics of MSCs, such as immune modulation and tissue damage repair ( 9 , 10 ). Our previous study also showed that human umbilical cord mesenchymal stromal cell-derived EVs (HuMSC-EVs) can protect cardiac cells against hypoxia/reoxygenation (H/R) injury via activation of the phosphoinositide 3-kinase (PI3K)/Akt pathway ( 11 ). However, the mechanism has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%